Efficacy of vericiguat in patients with chronic heart failure and reduced ejection fraction: a prospective observational study - Yinge Zhan; Liu Li; Jie Zhou; Yishan Ma; Xuchong Guan; Suo Wang; Ya Chang (BMC Cardiovascular Disorders)
Abstract Objectives This study aims to evaluate the therapeutic effect of Vericiguat through cardiopulmonary exercise testing (CPET) in patients with chronic heart failure and reduced ejection fraction (HFrEF). Methods A prospective observational study was conducted from May 2022 to May 2023, focusing on patients with HFrEF admitted to our hospital. Eligible patients were sequentially numbered and enrolled based on specific inclusion and exclusion criteria. They were divided into two groups: one receiving standard heart failure therapy and the other receiving standard therapy plus Vericiguat. Data were collected at baseline and at 1, 3, and 6 months post-discharge, including NT-proBNP, sST2, and echocardiographic assessments. All patients underwent CPET before discharge and again six months post-discharge for within-subject comparisons. Results The study enrolled 158 patients, with 79 in each treatment arm. No significant baseline differences were observed in the Weber Functional Classification or CPET parameters. At six months, the Vericiguat group exhibited a significant reduction in patients classified as C (from 31.6 to 7.5%) and D (from 31.6 to 3.7%), with P values less than 0.05. Additionally, Vericiguat significantly improved Peak Oxygen Consumption (from 14.24 ± 6.21 to 19.03 ± 4.87 ml/kg/min) and Anaerobic Threshold (from 10.48 ± 3.82 to 13.48 ± 3.31 ml/kg/min). Compared to the standard treatment group, the Vericiguat group demonstrated significantly higher Peak Oxygen Consumption, Anaerobic Threshold, and a lower Carbon Dioxide Equivalent Slope, with P values all below 0.05. Conclusions Vericiguat safely enhances exercise tolerance, as evaluated by CPET, in high-risk patients with HFrEF.